The Analysis User Experience Application of Working Capital Credit Withdrawal Approval Management Bank Indonesian People's Bank Using User Experience Quistionnaire Method - Hadi Sulaeman; Diky Wardhani (International Journal of Education, Information Technology, and Others, 2022)
In general, this study aims to describe the user experience of the BRI WA Management Capital Credit Application in order to support BRI's business, namely Working Capital Credit Withdrawal Approval where credit monitoring from disbursement to credit paid off requires special attention, the case study in this study was conducted at BRI KC Ciputat. The research method used in this study is a descriptive qualitative approach. The data collection process uses a user experience questionnaire to determine the user experience of the application. The data obtained from primary and secondary sources are then processed and analyzed to obtain answers or conclusions from the research conducted. The results of this analysis describe the level of user experience and explore user perceptions of the Working Capital Credit Application Withdrawal Approval Management of Bank Rakyat Indonesia showing the results in the Above average category (above average), namely on the attractiveness scale with a value of 1.52. Clarity scale with a value of 1.63. Accuracy scale with a value of 1.39. The stimulation scale scored 1.20. Novelty scale, get a value of 1.01. Meanwhile, on the efficiency scale, the score is 1.60 in the Good category. With these results, Bank Rakyat Indonesia's Working Capital Credit Application Withdrawal Approval Management felt the need to increase 5 scales to achieve better results. Especially on the Stimulation scale with the lowest benchmark comparison results in the category above the average of the other 5 scales with a value of 1.20